Antimicrobial therapy among hospitalized older adults with suspected infection and negative blood cultures - Galadriel Pellejero-Sagastizabal; Elena Morte-Romea; José Antonio Girón Ortega; José Ramón Paño-Pardo; Raquel Fernández Guerrero; Francisca Guerrero; Montserrat Montes de Oca; Silvia Jiménez-Jorge; Zaira R. Palacios-Baena; Jesús Rodríguez-Baño; Pilar Retamar-Gentil; Montserrat Montes de Oca Arjona; et al. (Antimicrobial Resistance & Infection Control, 2026)
Abstract Background Managing infections in older adults is challenging due to their unique characteristics, which often drives empirical antimicrobial use, increasing risks of adverse outcomes and antimicrobial resistance (AMR). Data on antimicrobial adequacy in older patients with suspected infection but negative blood cultures (BC) remain scarce, despite this being a common clinical scenario. Methods In this multicenter prospective cohort study (NO-BACT project) across three Spanish hospitals (2018–2019), we compared antimicrobial therapy adequacy between older adults (≥ 85 years) and younger patients with suspected infections and negative BC. Antimicrobial stewardship (AMS) experts evaluated treatment adequacy at days 2 and 5–7 using standardized guideline-based criteria. We assessed predictors of adequacy using logistic regression and examined clinical outcomes including 30-day mortality and length of hospital stay (LOS). Results Among 799 enrolled patients, 90 (11.3%) were older adults. While initial antimicrobial adequacy was comparable between groups at Day 2 (59.8% vs. 60.1%), older adults were significantly less likely to receive adequate treatment by Days 5–7 (adjusted OR 0.46, 95% CI 0.25–0.82, p = 0.009). The main drivers of inadequacy were excess antimicrobial spectrum (84.2%) and inappropriate route of administration (48.7%). Older adults demonstrated higher 30-day mortality (16.7% vs. 7.8%; p = 0.009) despite shorter LOS (8 vs. 10 days, p = 0.006), though treatment adequacy was not associated with mortality. Conclusions In older patients with negative BC, antimicrobial therapy shows high rates of inadequacy that worsen over time, primarily due to delayed de-escalation and prolonged intravenous therapy. These findings identify a clear target for AMS interventions focusing on timely treatment optimization.